PRİMER BÜLLÖZ AMFİZEMDE ANESTEZİ UYGULAMASI: OLGU SUNUMU - SALİHOĞLU, Ziya and KARACA, Saffet and KÖSE, Yıldız and DEMİROLUK, İ. Şener and DEMİRARAN, Yavuz (Cerrahpaşa Medical Journal, 2014)
Background.- Paraseptal emphysema is a kind of lung emphysema. In this emphysema, alveoles swells and connects with each other and eventually generates bullae in the lung. This state is named primary bullouse disease. The patients who have primary bullouse emphysema, anesthetic management must be chosen carefully, because mechanical ventilation can cause explotion of the bullae and this may result in pneumothorax. Observation.- In this case report we presented a patient with primary bullouse emphysema, context primary bullouse disease and its charecteristics.